How does institutional embeddedness shape innovation platforms? A diagnostic study of three districts in the Upper West Region of Ghana - Totin, Edmond; Roncoli, Carla; Sibiry Traoré, Pierre C.; Somda, Jacques; Zougmoré, Robert B. (Informa UK Limited, 2018)
Innovation platforms have emerged as a way of enhancing the resilience of agricultural and food systems in the face of environmental change. Consequently, a great deal of theoretical reflection and empirical research have been devoted to the goal of understanding the factors that enhance and constrain their functionality. In this article, we further examine this enquiry by applying the concept of institutional embeddedness, understood as encompassing elements of platform design, structure, and functions as well as aspects of the broader historical, political, and social context to which platforms are connected. We present a case study of sub-national platforms established in three districts of the climatically-stressed Upper West Region of Ghana and charged with facilitating climate change responses at the local level and channelling community priorities into national climate change policy. A different kind of organization − the traditional chief council, the agricultural extension service, and a local NGO − was chosen by members to convene and coordinate the platform in each district. We examine platform members’ accounts of the platform formation and selection of facilitating agent, their vision for platform roles, and their understandings of platform agenda and impacts. We analyse these narratives through the lens of institutional embeddedness, as expressed mostly, but not solely, by the choice of facilitating agents. We illustrate how the organizational position − and related vested interests − of facilitating agents contribute to shaping platform agendas, functions, and outcomes. This process hinges on the deployment of legitimacy claims, which may appeal to cultural tradition, technical expertise, community engagement, and dominant scientific narratives on climate change. Iinstitutional embeddedness is thereby shown to be a critical aspect of agency in multi-actor processes, contributing to framing local understandings of the climate change and to channelling collective efforts towards select response strategies. In conclusion, we stress that the institutional identity of facilitating agents and their relationship to members of the platform and to powerholders in the broader context provides a useful diagnostic lens to analyse the processes that shape the platform’s ability to achieve its goals.